2009
DOI: 10.1074/jbc.m804659200
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 Down-regulates Transforming Growth Factor-β (TGF-β) Signaling by Inducing Degradation of Smad Proteins

Abstract: Transforming growth factor-␤ (TGF-␤) is crucial in numerous cellular processes, such as proliferation, differentiation, migration, and apoptosis. TGF-␤ signaling is transduced by intracellular Smad proteins that are regulated by the ubiquitinproteasome system. Smad ubiquitin regulatory factor 2 (Smurf2) prevents TGF-␤ and bone morphogenetic protein signaling by interacting with Smads and inducing their ubiquitinmediated degradation. Here we identified Pin1, a peptidylprolyl cis-trans isomerase, as a novel prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
101
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 37 publications
5
101
0
1
Order By: Relevance
“…Previous studies in transformed human keratinocytes or prostate cancer cell lines have revealed TGF-␤1-induced interactions between Pin1 and phosphorylated Thr 179 -Pro 180 in the linker region of Smad3 (28,29). In addition, Pin1 knockdown had no effect on TGF-␤1-responsive genes in transformed keratinocytes but did suppress the migration and invasion of prostate cancer cell lines (29).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies in transformed human keratinocytes or prostate cancer cell lines have revealed TGF-␤1-induced interactions between Pin1 and phosphorylated Thr 179 -Pro 180 in the linker region of Smad3 (28,29). In addition, Pin1 knockdown had no effect on TGF-␤1-responsive genes in transformed keratinocytes but did suppress the migration and invasion of prostate cancer cell lines (29).…”
Section: Discussionmentioning
confidence: 92%
“…R-Smad linkers are also phosphorylated at Ser-Pro and Thr-Pro sites by MAPKs. In tumor cells, these sites in Smad3 are targets for Pin1, although the physiologic consequences or occurrence in normal cells remains unclear (28,29). To test this, lysates from primary Fb were immunoprecipitated with anti-Pin1 followed by immunoblot with anti-Smads.…”
Section: Blm or Saline Control Was Introduced Intratracheally (2) Intmentioning
confidence: 99%
“…This study shows in vitro as well as in vivo the inhibition of SMAD3 by cAMP and ACTH in the adrenal cortex. This differs from the gonads and reprogrammed tumor cells from pluripotent adrenocortical stem/progenitors adopting a gonad-like differentiation after inhibin a inactivation (39,40). This difference also underlines the tissue-specific effect of cAMP pathway dysregulation in tumorigenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Although repression of TGFb signaling by Smad linker phosphorylation was attributed to inhibition of nuclear translocation of Smad2 and Smad3 (10), and proteasomal degradation of Smad3 through poly-ubiquitination (31,32), mice with targeted-disruption of Smurf2 allele have now unveiled Smurf2 binding to the phosphorylated Smad3 linker regions in vivo and subsequent induction of multiple mono-ubiquitination at the MH2 domain, leading to a negative regulation of TGFb signaling by inhibiting the formation of Smad3 complexes acting on target genes (33). This provides a molecular mechanism by which the EPSM has increased transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%